1982
DOI: 10.1111/j.1151-2916.1982.tb10509.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nuclear Waste Glass Leaching by Chemisorption

Abstract: The durability of a simulated nuclear waste containment glass was investigated by static leaching tests in six types of leaching containers. Glass corrosion in lead containers was reduced by more than two orders of magnitude from that measured in Teflon, whereas aluminum containers resulted in nearly a one order of magnitude reduction. Relatively minor effects on glass leaching were measured in copper, tin, and titanium containers. The results have strong implications concerning the choice of materials in poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Many experimental studies have looked at the effects of other repository materials on glass dissolution rates: i.e., with tuff present [130][131][132][133][134] [21,131,140]. Good reviews of interactions between repository material and glass are found in Werme et al [84] and Bibler and Jantzen [134].…”
Section: Interactions With Other Repository Materialsmentioning
confidence: 99%
“…Many experimental studies have looked at the effects of other repository materials on glass dissolution rates: i.e., with tuff present [130][131][132][133][134] [21,131,140]. Good reviews of interactions between repository material and glass are found in Werme et al [84] and Bibler and Jantzen [134].…”
Section: Interactions With Other Repository Materialsmentioning
confidence: 99%
“…They revealed that glass dissolution rate strongly vary depending on factors such as pH [14,15], temperature [16,17], elements in solution (Zn [18]; Pb [19]; Fe [20], Si [15,21], Al [22,23], S/V ratio [24,25] flow rate [26][27][28] and glass composition [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Hench et al [43, 45, 5 l] suggested that the leaching behavior of nuclear waste glass is largely a function of the surface composition; Hench and Clark [51] have categorized glass surfaces into five types, based on the composition profile. Most discussions in the literature regarding the role of the alteration surface layers in glass reaction concentrate on whether the surface layers form physical mass transport (diffusion) barriers that inhibit further glass reactions by impeding the transport of reactants and products to or from the reaction zone [23, [52][53][54][55][56][57][58][59][60][61][62]. Observed decreases in leach rate with time can also be attributed to the approach to saturation limits of glass components in solution [32,[63][64][65][66].…”
Section: Surface Layers As Mass Transport Barriersmentioning
confidence: 99%